Reja Dorada. (The Golden Gate.) Polka - I.E. Hernandez::::::::: (Eduardo Gariel)
Piano score, 8 p. On cover: Edicion especial para la Exposicion Colombiana de Chicago 1893. Respectfully dedicated to Mr. J. von Helms, Captain of the Steamer Neubern. Publishers advertisement on verso of last leaf.